ANALYSIS OF SURPLUS-DEFICIT IRRIGATION WATER PAMUKKULU TAKALAR REGENCY, SOUTH SULAWESI - Farida, Sitti Nur (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2015)
Irrigation areas with specific technical, will have acertain pattern as well and irrigation water available is influenced by the condition of water resources and management, The successin the management of irrigation water is determined by the balance of irrigationwater available andthe requiredwater. This researchwas carried out by predicting potentialwater resources useWatershedModeling System, calculate cropwater requirements to determine the surplus-deficit water. The results were obtained monthly discharge based predictionWMS 1,32- 24,7 m3/sec, which the lowest discharge in September and the highest in February. Crop water requirements, shortage ofwaterf or 7months (May-November). Utilization of the damme driverwater at the weir Pamukkulu can supply these needs, with a surplus of water, 0,1-3,85m3/sec/month.